Carbapenem-Resistant Klebsiella pneumoniae Isolated From a Patient in a Midwestern U.S. Hospital With a History of Indian Travel: Therapeutic Strategies and Clinical Outcomes - Christopher Phan; Kristen Tsai; Christian M. Gill; Robin Chamberland; Christian Hendrix; Rong Hou (Case Reports in Infectious Diseases)
Carbapenemases have had increasing prevalence within the United States and worldwide. Here, we present a case of carbapenem-resistant Klebsiella pneumoniae (CRKP) which is unique due to the rarity of multiple mechanisms of resistance within the Klebsiella pneumoniae harboring New Delhi metallo-β-lactamases (NDM), oxacillinase-48 (OXA-48)-like, and cefotaximase (CTX-M) resistance genes, detected in a patient following an international travel. This case demonstrates the need for a multidisciplinary approach to optimize the treatment of multidrug-resistant Gram-negative organisms.